PERLINDUNGAN HUKUM INDIKASI GEOGRAFIS TERHADAP PRODUK PERTANIAN PROVINSI ACEH - WANTI ELVIRA (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Saidin, SH, MHum2. Dr. T. Keizerina Devi A, SH, CN, MHum3. Dr. Jelly Leviza, SH, MHumGeographical indication is a sign indicating the origin of goods and/or products due to their geographical environments including the nature, man, or the combination of both which contribute to reputation, quality and particular characteristics of the goods and or products produced. The goals of the protection for geographical indication are to protect the specialization from replicating or misusing, to provide a chance and protection for local people to produce typical products to obtain maximum advantage, to benefit the consumers because the quality of products is guaranteed. This is an empirical normative judicial research with analytical descriptive. The result demonstrates that there are some agricultural products which are potentialto be regiostered as geographical indications in Aceh Province. The causative factor of why potential products for geographical indications are not yet registered is because the local people do not have a legal awareness, minimum fund, nonexistent of forum for society who care to protect and register the commodities, lack of requirements for geographical indication, and lack of cooperation among local people producing the products to be registered. Government of Aceh Province keeps on providing legal protection to protect the existing agriculutural products either the ones which indicate potential to be registered as geographical indication or the ones which have been registered.Keyword: Agricultural Product, Geographical Indication